Posterior Cortical Atrophy: Characteristics From a Clinical Data Registry - Jennifer J. Olds; William L. Hills; Judith Warner; Julie Falardeau; Lori Haase Alasantro; Mark L. Moster; Robert A. Egan; Wayne T. Cornblath; Andrew G. Lee; Benjamin M. Frishberg; Roger E. Turbin; David M. Katz; et al. (Frontiers in Neurology, 2020)
Background: Posterior cortical atrophy (PCA) is a neurodegenerative syndrome that presents with higher-order visual dysfunction with relative sparing of memory and other cognitive domains, and it is most commonly associated with Alzheimer's disease pathology. There is a lack of data regarding the presentation of PCA to non-cognitive specialists. Therefore, we collected clinical data from neuro-ophthalmologists regarding the presentation of PCA to their practices and compared data to published cohorts and a published survey of cognitive specialists.Methods: Members of the North American Neuro-Ophthalmology Society Listserv (NANOSnet) were invited to complete an online, retrospective, chart-review data-entry survey regarding their patients with PCA, and REDCap was used for data collection.Results: Data for 38 patients were entered by 12 neuro-ophthalmologists. Patient mean age at presentation was 67.8 years, and 74% of patients were women. Difficulty reading was reported at presentation by 91% of patients, and poor performance on color vision, stereopsis, and visual field testing (performed reliably by 36/38 patients) were common findings. Most patients who were treated were treated with donepezil and/or memantine.Conclusions: Compared to published data from cognitive specialists, patients presenting to neuro-ophthalmology with PCA were more likely to be older and female and have a reading complaint. Reliable visual field testing was the norm with homonymous defects in the majority of patients. The neuro-ophthalmologist plays an important role in diagnosing PCA in older adults with unexplained visual signs and symptoms, and future studies of PCA should involve multiple specialists in order to advance our understanding of PCA and develop effective treatments.